Katliamın Yirminci Yılında Türk Basınında “Hocalı” Yaklaşımı - Yılmaz, Reha (Fırat University, 2013)
Milletlerin tarihinde öyle dönemler, öyle olaylar vardır ki, onlar talihin kırılma noktalarıdır. Eza cefa, acı vardır buralarda. Türkün kanı vardır, acılı anaların dimağında yavrusunun masum yüzünde. Türkün makus talihidir. Büyük millet olmasının bir neticesi. Affeder, bir şans daha verir, sofrasına buyur eder. Sohbetine ortak. Ama bunu anlamazsa zalim, bir Kürşat kalkar isyan eder, ötelerden Bilge Kağanlar, bugünlerde Atatürkler, Haydar Aliyev’ler çıkar. Dur der zalime uzattıysak elimizi acizliğimizden değildir. Yeri geldiğinde göstermesini de biliriz ulu başımızı, eğilmez bileğimizi.

In 2012, twenty years have passed since Khojaly Massacre. Varieties of activities have been organized by the Azerbaijan government to learn and accept the massacre as genocide in the world under “Khojaly Justice” slogan. In this context, various activities have been organized in Turkey, on 26.02.2012 thousands of people gathered in Taksim Square to remember the victims of the Khojaly Massacre. Looking at the reflections of the Turkish press both before and after the meeting in Taksim, it is seen that despite the twenty years left behind, all the facts of massacre are not known and understood. It is possible to classify the reasons as follow: 1. Wrong promotion policy, 2. Owned of the subject by only a certain section in Turkey, 3. Double standards and, 4. Back-breaking labour of the Armenian lobby. In this context, it is apparent that Azerbaijan government needs to change policy for promoting Turkish public opinion, especially media representatives on Khojaly Massacre
Turkish Press Approach in the Twentıeth Anniversary of the “Khojaly” Massacre